The profile of people with Parkinson’s disease included in community boxing exercise programs - Domingos, Josefa (2021)
Exercise is widely recommended for people with Parkinson (PD). Boxing is a popular mode of training. However, including individuals with less favorable profiles may have a negative impact on participation. We performed a systematic review to study the patient characteristics that were included in boxing exercise programs research and reflect on the possible inclusion criteria that professionals can use for boxing exercise programs. Indications for the best profiles were limited due to the small number of studies. Boxing programs should include people with the diagnosis of PD in earlier stages, independently ambulatory, and without current severe musculoskeletal or cardiovascular conditions.